2013
DOI: 10.1371/journal.pone.0068818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus amyloliquefaciens FZB42 on Lettuce Growth and Health under Pathogen Pressure and Its Impact on the Rhizosphere Bacterial Community

Abstract: The soil-borne pathogen Rhizoctonia solani is responsible for crop losses on a wide range of important crops worldwide. The lack of effective control strategies and the increasing demand for organically grown food has stimulated research on biological control. The aim of the present study was to evaluate the rhizosphere competence of the commercially available inoculant Bacillus amyloliquefaciens FZB42 on lettuce growth and health together with its impact on the indigenous rhizosphere bacterial community in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
154
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(184 citation statements)
references
References 44 publications
13
154
2
4
Order By: Relevance
“…Plating and low-throughput molecular techniques showed that BCA treatment altered microbial community diversity and abundance. (Buddrus-Schiemann et al, 2010;Chowdhury et al, 2013;Teixidó et al, 1998;Yin et al, 2013;Zhang et al, 2008). These results show that a BCA has an impact on the plant microbiome.…”
Section: Microbiome Responses To Bcas or Pathogen Applicationmentioning
confidence: 77%
See 2 more Smart Citations
“…Plating and low-throughput molecular techniques showed that BCA treatment altered microbial community diversity and abundance. (Buddrus-Schiemann et al, 2010;Chowdhury et al, 2013;Teixidó et al, 1998;Yin et al, 2013;Zhang et al, 2008). These results show that a BCA has an impact on the plant microbiome.…”
Section: Microbiome Responses To Bcas or Pathogen Applicationmentioning
confidence: 77%
“…Several studies evidenced that factors like soil properties, experimental conditions and physiological state had a deeper and more durable effect on the rhizosphere microbiota than BCA application (Chowdhury et al, 2013;Grosch et al, 2006;Kröber et al, 2014;Scherwinski et al, 2007;Schreiter et al, 2014b). The effect of a BCA can also depend on its interaction with other factors: amplicon sequencing analysis revealed significant modifications of the bacterial community composition of lettuce rhizosphere following application of the BCA P. jessenii RU47 in alluvial loam, but not in diluvial sand or loess loam (Schreiter et al, 2014a).…”
Section: Microbiome Responses To Bcas or Pathogen Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, using plating and low-throughput molecular techniques, reported that the introduction of a biocontrol agent or a pathogen to the system had a marked impact on the plant microbiome (Teixidó et al, 1998;Zhang et al, 2008;BuddrusSchiemann et al, 2010;Chowdhury et al, 2013;Yin et al, 2013). Erlacher et al (2014) demonstrated shifts in the microbiota of lettuce as a result of introducing a pathogen (Rhizoctonia solani) and/or a biocontrol agent.…”
Section: The Role Of the Microbiome In Fruit Health And Disease à A Nmentioning
confidence: 99%
“…The ability of members of the Gram-positive genus Bacillus to form spores is advantageous for controlling a variety of soil-borne phytopathogenic fungi [23][24][25][26][27], and some are commercially marketed as biopesticides, biofertilizers and soil amendments because of their easy colonization, good competition and broad antimicrobial spectrum [28][29][30][31][32]. For example, these bacteria: B. subtilis B579 [33], B. subtilis N7 [34], B. amyloliquefaciens SQR-9 [35], Pseudomonas fluorescens [15,36] are effective biocontrol agents.…”
Section: Introductionmentioning
confidence: 99%